Different Categories of Business Risk - Simona-Valeria TOMA; Ioana-Veronica ALEXA; Daniela SARPE (Risk in Contemporary Economy, 2011)
Every business organisation involves some element of risk. Unmitigated risks can result in lost opportunity, financial losses, loss of reputation, or loss of the right to operate in a jurisdiction. Like any other risk type, understanding business risks is quite important for every business to garner profits instead of facing losses. A business risk is a universal risk type; this means that every business in the world faces business risks. Therefore, it is imperative to understand the different categories of business risk in order to create the appropriate strategies. The aim of this paper is to describe the most important categories of business risks and to make sure that every type of risk receives equal treatment and consideration.